Mid‐IR transparent TeO2‐TiO2‐La2O3 glass and its crystallization behavior for photonic applications. Issue 9 (14th April 2018) - Gupta, Gaurav; Balaji, Sathravada; Biswas, Kaushik; Kalyandurg, Annapurna
Abstract: In this report, effect of enhanced rare earth (La2 O3 ) concentration on substitution of TeO2 within ternary TeO2 ‐TiO2 ‐La2 O3 (TTL) glass system has been studied with respect to its thermal, structural, mechanical, optical, and crystallization properties with an aim to achieve glass and glass‐ceramics having rare‐earth‐rich crystalline phase for nonlinear optical and infrared photonic applications. DSC analysis (10°C/min) demonstrates a progressive increase in glass‐transition temperature ( T g ) from 359 to 452°C with the increase in La2 O3 content. Continuous glass network modification with transformation of [TeO4 ] to [TeO3 /TeO3+1 ] units is evidenced from Raman spectra which is corroborated with XPS studies. While mechanical properties demonstrate enhancement of cross‐linking density in the network. These glasses exhibit optical transmission window extended from 0.4 to 6 μm with calculated zero dispersion wavelength (λZDW ) varying from 2.41 to 2.28 μm depending upon La2 O3 content. Crystallization kinetics of TTL10 (80TeO2 ‐10TiO2 ‐10La2 O3 in mol%) glass has been studied via established models. Activation energy ( E a ) has been evaluated and dimensionality of crystal growth ( m ) suggests formation of surface crystals. Glass‐ceramic with crystalline phase of La2 Te6 O15 has been realized in heat‐treated TTL10 glass samples (at 450°C). As predicted from DSC analysis, FESEM study unveils the formation of surface crystallized glass‐ceramics.